Strategi Rasulallah Dalam Pendidikan Perspektif Tafsir Tarbawi - Alam Tarlam; Abdullah Zaky; Anwar Musyaddat (Al-Mau'izhoh, 2023)
The Islamic religion with all its perfection has provided guidance on all aspects of life, including aspects of education as one of the most important aspects for humans. Al-Qur'an becomes guidance and guidance in the journey of the Prophet's struggle in the world of education. However, whether the theory and methods of Rasulullah in the Qur'an are relevant to today's education, this becomes a dilemma and the writer tries to examine it. This paper aims to find out how Rasulullah's strategy is in developing education from the perspective of tarbawi interpretation, through textual and contextual understanding studies. Existing problems are answered through library research. The data were collected from various references: both primary, secondary, and supporting data. The results of the study show that Rasulullah's Methods and Strategies in the world of education can have a very large influence both in the classical period and the present, this proves that educational theory in Islam can be applied and utilized for the development of students in various institutions, elementary, secondary schools first, upper secondary to tertiary level.